2016
DOI: 10.1177/0020764016629699
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the prevalence of mental illness stigma within the Greek culture

Abstract: The review highlights the wide-scale prevalence of mental illness stigma within the Greek culture and the need for further rigorous research including culturally tailored stigma interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 41 publications
2
25
1
1
Order By: Relevance
“…Third, the sample was predominantly Caucasian. Hence, our findings may not extend to other cultures (e.g., Greek, Caribbean, Latin American, Asian) where perceptions of mental health problems may differ (Mascayano et al, 2016;Tzouvara, Papadopoulos, & Randhawa, 2016). Fourth, we did not explicitly ask participants about the effectiveness of their coping or resilience strategies.…”
Section: Limitations!mentioning
confidence: 92%
“…Third, the sample was predominantly Caucasian. Hence, our findings may not extend to other cultures (e.g., Greek, Caribbean, Latin American, Asian) where perceptions of mental health problems may differ (Mascayano et al, 2016;Tzouvara, Papadopoulos, & Randhawa, 2016). Fourth, we did not explicitly ask participants about the effectiveness of their coping or resilience strategies.…”
Section: Limitations!mentioning
confidence: 92%
“…The level of mental-health-related stigma among young people in India remains unknown. Stigma research in the United States, Greece, and Japan [20][21][22] identifies social distance and discriminatory beliefs related to mental health problems and a systematic review found stigma of mental disorders associated with violence, unpredictability and disability in Latin America and the Caribbean [23]. With the largest young population in the world at 365 million, [24] and a large burden of untreated mental health problems, young people in India will likely face challenges in achieving their social and economic potential.…”
Section: Introductionmentioning
confidence: 99%
“…: . В ряде культур проблема стигматизации обусловлена к тому же различными социальными аспектами и принятыми в кон кретном обществе нормами Tzouvara et al, 2016). Роль стигмы как серьезного препятствия для выявления симптомов психических расстройств, нарушений психического здоровья и обращения за помощью является предметом дискуссий в области культурной обусловленности психического здоровья.…”
Section: культура и стигма при обращении за психологической и психотеunclassified